DAKWAH PEMBANGUNAN DALAM PRODUKSI SIARAN RADIO DAN TELEVISI - ., Surianor (UIN Antasari Banjarmasin, 2012)
Development requires a model of socialization with various approaches, one of them is a religious approach. The media, both print and electronic have the trategic position and role in delivering development message.. Radio and television should proactively communicate and preach the message of development to the community, with the hope that people are inspired to help and participate, in order to achieve success in various aspects of development. The problem is the role of public broadcasting services in preaching the dakwah of development is still lacking, and broadcasting companies are more commercially oriented and mostly owned by nonMuslims. Commitment and the role of Muslim entrepreneurs are needed to set up, manage and develop broadcasting services that are more focused on the interests of dakwah